Medication Errors. Issue 8 (August 2016) - Cohen, Michael R.
Abstract : Minimize the use of disinfecting caps on pediatric I.V. catheter hubs and ports...beware confusing labeling on blister pack for cystic fibrosis medication...keep vaccines in storage units dedicated exclusively to vaccines